DEVELOPING STUDENT’S ENGLISH SPEAKING SKILL WELL IN 8 HOURS - Tarmizi Rasul (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2014)
The objective of this research is to develop the Students’ English speaking skillof class HIJ 49 students semester 1 2013/2014 at Indraprasta University Faculty of Art and languages English Department since the data showed that 85.40% of the students semester one were not able to speak English. There were some problems which made the students unable to speak English. One of them was method. The method which was used to develop the students’ English speaking skill was “Oral Questioning.” The Finding showed in the first segment on the first circle that the students looked confused since they were not accustomed to speaking English by oral Questioning in their first language (L1) method. The second segments of the first circle indicated that they had understood how to speak English grammatically, After being tested by an English lecturer as a collaborator at the end of the third of the first segment resulted that 80 % of the students reached the minimal scores 72. At last, at the end of two segments of the second circles of the second test showed that 100% of the students were able to speak English confidently: The average scores were 81.61, modus score was between 78 until 81 or 36.73%.Keywords: Speaking, English